Medical comorbidities in Saudi patients with narcolepsy: a case-control study - Ahmed Salem BaHammam (Brazilian Association of Sleep and Latin American Federation of Sleep Societies, 2021)
Objective: This case-control study sought to assess comorbid medical disorders in patients with narcolepsy type-1 (NT-1) and type-2 (NT-2). Material and Methods: he study comprised 80 consecutive Arab (Saudi) patients with narcolepsy (NT-1=56 and NT-2=24) and a control group of 211 adults matched for age, sex, and body mass index (BMI). Data were collected from cases and controls based on a predesigned questionnaire that was formulated based on previous studies to evaluate the chosen medical comorbidities. Results: Narcolepsy patients had a higher prevalence of hypothyroidism and hyperlipidemia and a higher prevalence of high-risk for OSA than controls. Hyperlipidemia was more common in cases than controls, 8 (10%) vs. 3 (1.4%), p=0.002. After adjusting for age, sex, and BMI, the odds-ratios for hypothyroidism and high risk for OSA in the NT-1 group was 5.49 (95% CI, [0.8 - 38.6]) and 69.99 ((95%CI [20.6 -237.4]), respectively, and in the NT-2 group, 12.5, 95%CI [1.6-97.7], and 33.3, 95%CI [8.2-135.7], respectively. Conclusion: Arab (Saudi) narcolepsy patients had a higher association with hypothyroidism, hyperlipidemia, and a higher risk of OSA than controls.